2011
DOI: 10.1186/1756-3305-4-171
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Metarhizium anisopliae of low and high virulence by mating behavior in Aedes aegypti

Abstract: BackgroundDengue is a viral disease transmitted by Aedes mosquitoes. It is a threat for public health worldwide and its primary vector Aedes aegypti is becoming resistant to chemical insecticides. These factors have encouraged studies to evaluate entomopathogenic fungi against the vector. Here we evaluated mortality, infection, insemination and fecundity rates in A. aegypti females after infection by autodissemination with two Mexican strains of Metarhizium anisopliae.MethodsTwo M. anisopliae strains were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…Similarly, this competition for nutrients between the host and fungus, could also explain the 52% reduction in fecundity and a shortening of the GC from 5 to 3 days in B3. In a previous study, we conducted with this fungus but with a highly virulent strain (Ma-CBG-2) found that in mycosed females the fecundity was reduced to almost zero [7]. In addition, the Anopheles gambiae female mosquitoes tend to take smaller blood meals after becoming fungus-infected [29], [30] and this also plausibly explains the reduced number of females which actually laid eggs.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, this competition for nutrients between the host and fungus, could also explain the 52% reduction in fecundity and a shortening of the GC from 5 to 3 days in B3. In a previous study, we conducted with this fungus but with a highly virulent strain (Ma-CBG-2) found that in mycosed females the fecundity was reduced to almost zero [7]. In addition, the Anopheles gambiae female mosquitoes tend to take smaller blood meals after becoming fungus-infected [29], [30] and this also plausibly explains the reduced number of females which actually laid eggs.…”
Section: Discussionmentioning
confidence: 82%
“…aegypti mosquitoes were exposed to single infections of either Ma-CBG-1 M. anisopliae strain at 1.6×10 8 conidia mL −1 (SF) or DENV-2 (SV); and both fungus and virus (CI). Fungal infections were done as described previously [7]. For the virus infections, females were confined in 1-liter glass flasks, and were fed on 2,320 µL defibrinated human blood and 680 µL of virus suspension containing a titer of 1×10 7 plaque-forming units (PFU) mL −1 , for 1 hour via a water-jacketed membrane feeding apparatus [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conidia could eventually be dispersed by contaminated females that leave the fungus‐infested substrate after oviposition (Reyes‐Villanueva et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…To date around forty experimental studies have been reported examining some aspect of fungal infection on adult mosquito vectors [12,13,15-19,21-24,31-57]. These studies include multiple fungal isolates from eight genera and twenty-one species.…”
Section: Introductionmentioning
confidence: 99%